Training for MSMEs on Leveraging Social Media for Online Marketing - Jemest Streit Kaweke (Akademi Sertifikasi Profesi Internasional, 2025)
This service bridges the significant disparity between the vast potential of the digital market and the inadequate digital literacy skills prevalent among Small and Medium Enterprises (SMEs). The primary challenge confronting SMEs is their incapacity to convert social media platforms, such as Instagram and TikTok, from simple communication tools into potent sales mechanisms, resulting in a competitive disadvantage against more agile commercial entities. This program aims to provide practical training and direct support to help SMEs improve their skills in creating, planning, and analyzing marketing content that works well with digital platform algorithms. This program's innovation is in the Content-to-Commerce (C2C) Model, which integrates engaging visual content with direct connectivity to WhatsApp Business and marketplaces, alongside an emphasis on straightforward metric analysis. The results showed that during the mentorship period, SME accounts had a 45% boost in engagement, a 30% growth in followers, and a notable 20% rise in sales conversions